MOTIVE OF THE 'RAN AWAY' OF STUDENTS IN ONE OF THE TAHFIZ ISLAMIC BOARDING SCHOOL IN BOGOR - Anwar; Said Ma’ruf (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to find out to what extent the motives of students at the Tahfiz Al-Qur'an Islamic boarding school who often “ran away”, both at night and in the morning. Even though regulations and sanctions have been implemented, the deterrent effect on students has not made any changes. This research uses a qualitative method with a phenomenological approach which is used to understand the